The frequency of gene targeting in yeast depends on the number of target copies. - Wilson, J H (1994)
We have compared the efficiency of transformation by linear DNA fragments in yeast strains carrying different numbers of homologous targets for recombination. In strains carrying dispersed copies of a target and in strains carrying tandem arrays, the frequency of transformation is proportional to the number of targets. This result is in contrast to previous studies of transformation in mammalian cells, where targeted integration was insensitive to the number of targets. We conclude that, in yeast, the search for a homologous partner is a rate-limiting step in the successful recombination of linearized DNA fragments. Furthermore, the fact that we obtain the same results with both dispersed and clustered targets argues against models of homology searching in which DNA becomes nonspecifically associated with a chromosome and then slides along the DNA until homology is encountered.